Literature review on barriers to digital transformation and its relationship with the financial performance - Ahomed, Rubén (2020)
Digital transformation is an activity that companies have been adopting to take advantage of digital technology developments and stay at the business forefront profitably. The purpose of this analysis is to review the literature related to digital transformation, the barriers to achieving it and its financial performance. Through a review of 59 articles, a conceptual framework was defined with nine definitions for digital transformation, nine for barriers to innovation and five for financial performance. The main findings are that there are barriers to the development of the digital business transformation, but they differ according to the industry and country. On the other hand, the financial benefit is not clear and depends on the context.